Pentingnya Interaksi Hidrogen dengan Nitrogen Backbone di Situs FS918 pada VEGFR2 Berdasarkan Analisis 31 Struktur Kristal VEGFR2 - Maranantan, Fandriastika; Christy, Anintia Mara (Jurnal Farmasi (Journal of Pharmacy), 2012)
Polar interactions was observed from 31 VEGFR2 crystal structure using PyMOL 1.2r1.The interactions was seen in form of direct and indirect interactions. From visual observation shows that  nitrogen  backbone  direct  interaction  in  site  FS918  is important  because  approximately  87%  of  the  entire  VEGFR2 crystal structure has this interaction (from 31 crystal structure only 4 that has not interaction)